Cross-Sectoral Strategies for Freshwater and Sanitation in Supporting Sustainable Environmental Resilience - Djansena, Alradix; Erika, Katherine; Santoso, Budi (PPSDP International Journal of Education, 2025)
This study explores the strategic role of freshwater and sanitation management in supporting sustainable environmental resilience in Indonesia. Employing a qualitative systematic review method, the research analyzes interdisciplinary literature, policy documents, and case studies to identify structural challenges and effective responses. Key findings reveal persistent issues including water pollution, unequal distribution, poor sanitation access, and fragmented governance. The study highlights the success of community-based initiatives like SANIMAS and proposes the integration of low-cost technologies such as anaerobic waste treatment and household filtration systems. The novelty of this research lies in its cross-sectoral approach that bridges environmental policy, public health, and social participation. It argues for holistic governance reforms, enhanced stakeholder collaboration, and policy harmonization to ensure efficient freshwater and sanitation management. The study contributes strategic recommendations tailored to Indonesia’s context, emphasizing the synergy of government, private sector, and community actors. It also underscores the relevance of water-energy-food nexus thinking in national planning. Ultimately, this research supports Indonesia’s progress toward achieving SDG 6 (clean water and sanitation) and SDG 13 (climate action), reinforcing freshwater and sanitation as critical pillars for long-term resilience, public well-being, and sustainable development.